2014
DOI: 10.1017/sjp.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

Anger in Pathological Gambling: Clinical, Psychopathological, and Personality Correlates

Abstract: The aim of this study was to explore the association between pathological gambling (PG) and anger by assessing whether psychopathology and personality are related to PG and to evaluate gender differences. The sample comprised 71 PGs and 37 healthy controls. Anger, psychopathology and personality were assessed with the STAXI-2, SCL-90-R and TCI-R respectively. Gender did not affect anger expression after stratifying by diagnostic condition (p > .05). Among PG patients, anger, psychopathology and personality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…From a clinical perspective, these findings could be understood taking into account that certain personality traits or domains could be associated with a greater or lesser degree of psychopathology or emotional distress, as shown in previous research (3337). Specifically, according to the results, the personality trait most closely associated with psychopathology or emotional distress was harm avoidance.…”
Section: Discussionmentioning
confidence: 87%
“…From a clinical perspective, these findings could be understood taking into account that certain personality traits or domains could be associated with a greater or lesser degree of psychopathology or emotional distress, as shown in previous research (3337). Specifically, according to the results, the personality trait most closely associated with psychopathology or emotional distress was harm avoidance.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have linked GD with anger and with aggressive behaviors and violence (Cunningham-Williams et al, 2009 ; Dowling et al, 2014 ). There is also some evidence of a relationship between high novelty seeking, hostility, anger and severity of GD in treatment-seeking individuals (Aymamí et al, 2014 ). Some authors found that people with GD reported a lower level of awareness or insight into their emotions than healthy controls (Williams et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between high impulsivity and emotional dysregulation has also been described in young adults (Schreiber et al, 2012 ). Various studies contend that personality traits related to impulsivity in GD (such as novelty seeking, lack of emotional control, and lack of planning) are positively associated with anger expression (Schwebel et al, 2006 ; Aymamí et al, 2014 ) and a lack of anger control (Truglia et al, 2006 ). Emotional regulation (ER) can be considered as a specific example of general self-regulation patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological risk factors included the previous history of gambling problems and the evidence of personality traits consistent with GD (Claes et al, 2012 ; Aymamí et al, 2014 ; Granero et al, 2014 ), including high impulsivity and low self-directedness. In fact, this latter dimension is maintained at a low level regardless of age (Granero et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%